STUDI PENGHAYATAN CINTA LINGKUNGAN SISWA DAN MAHASISWA DI PERKOTAAN (STUDI KASUS DI BEBERAPA SEKOLAH MENENGAH ATAS DAN UNIVERSITAS DI KOTA SEMARANG) - Susilowati, Indah (Universitas Muhammdaiyah Surakarta, 2003)
Due to economic and political turbulencies in Indonesia people are becoming less aware in paying attention to their environment. Younger group might has a better awareness to the environment than the adults ones. This study aims to explore the behavior of younger peoples awareness in Semarang City towards the environment.Four hundred and ten students and key-persons such as selected teachers and lecturers, headmasters, and other competent persons had have been interviewed. Descriptive statistics was employed to explain the behavior of respondents in environmental awareness.The study found that respondents in higher school have relatively better attitudes to their environments than respondents in university. It is suggested that we need to reform curriculum and teaching-and-learning processes in conducting formal education with sufficient color of environment. The role of parents and guardians are urgently important to attain the expected environment-awareness.